(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
this article describes in detail the reforms implemented in the internal affairs bodies, coercive measures applied to minors, the procedure for placement of minors in special educational institutions, minors placed in educational institutions of the Republic.